Multipartite Entanglement Generation Assisted by Inhomogeneous Coupling - Retamal-Abarzua, J; Lopez-Cabrera, C (2012)
We show that controllable inhomogeneous coupling between two-level systems and a common data bus provides a fast mechanism to produce multipartite entanglement. Our proposal combines resonant interactions and engineering of coupling strengths-between the qubits and the single mode-leading to well-defined entangled states. Furthermore, we show that, if the two-level systems interact dispersively with the quantized mode, engineering of coupling strengths allows the controlled access of the symmetric Hilbert space of qubits. © 2012 American Physical Society.